2020
DOI: 10.31015/jaefs.2020.3.14
|View full text |Cite
|
Sign up to set email alerts
|

How does the environmental knowledge of Turkish households affect their environmentally responsible food choices? The mediating effects of environmental concerns

Abstract: The main objective of the present study is to examine whether Turkish households' environmental knowledge effects environmentally responsible food choices through the mediating effect of households' environmental concerns. A face-to-face survey was conducted, resulting in 450 responses from households that have recently chosen environmentally responsible foods in Erzurum, Turkey. The hypotheses were tested using the partial least squares-based structural equation modelling (PLS-SEM) technique to detect how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In cross-loading, the factor loading indicators on the assigned construct should be higher than those of other constructs under the condition that the cut-off value of the factor loading is higher than 0.70 (Table 1) [29,30]. The second measure for discriminant validity is the HTMT ratio of correlation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cross-loading, the factor loading indicators on the assigned construct should be higher than those of other constructs under the condition that the cut-off value of the factor loading is higher than 0.70 (Table 1) [29,30]. The second measure for discriminant validity is the HTMT ratio of correlation.…”
Section: Resultsmentioning
confidence: 99%
“…The second measure for discriminant validity is the HTMT ratio of correlation. Basar and et al [29] proposed that the performance of this method was superior. Using the Monte Carlo simulation, they found that HTMT achieved higher specificity and sensitivity rates (97-99%) than the cross-loading (0.00%) and Fornell-Larcker (20.82%) criteria.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the environmentally responsible food choices of individuals, the 7-item “Environmentally Responsible Food Choices” instrument developed by Başar was used ( 17 ). The items are as follows: “I can pay more for organically grown food,” “I avoid consuming food with genetically modified organisms (GMOs),” “I prefer to consume eco-label food,” and “I am careful not to consume too much meat,” “I prefer to buy dairy products from local producers,” “I avoid consuming imported food such as a variety of exotic fruits,” and “I avoid consuming canned “ready-made” food.” Item responses are 5-point Likert type and each item is scored between 1 and 5.…”
Section: Methodsmentioning
confidence: 99%
“…It is thought that our study would be important in terms of filling this gap in the literature. Furthermore, practices such as eco-labeling are considered an important indicator of the increase in individuals’ awareness of environmentally responsible foods and their interest in these products ( 17 ). Therefore, it is regarded as essential to evaluate the preferences of individuals for traditional/local foods, products with environmental labels, and especially ultra-processed foods in food preferences within the framework of sustainable nutrition.…”
Section: Introductionmentioning
confidence: 99%